2022
DOI: 10.3390/su14169921
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Network Structure of Tourism Efficiency and Its Influencing Factors in China: A Social Network Analysis

Abstract: Although tourism has gradually become a popular form of leisure and entertainment in China, the quality of China’s tourism development remains unclear. Through the panel data of 30 provinces in China, an SBM-DEA model and a social network analysis are used to explore the quality of tourism development, and a spatial econometric regression is used to identify the relevant factors affecting tourism efficiency. The study found that the level of tourism efficiency in Southwest China is high and stable. The northwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Other inputs. We use the number of A-class scenic spots, star-rated hotels and travel agencies as other input indicators to reflect the level of service input and infrastructure construction of tourism industry and to a certain extent to make up for the lack of land input elements [32]. The main sports industry unit is a vital carrier for the development of sports industry and a key indicator to reflect the development scale of the industry.…”
Section: • Input Indexmentioning
confidence: 99%
“…Other inputs. We use the number of A-class scenic spots, star-rated hotels and travel agencies as other input indicators to reflect the level of service input and infrastructure construction of tourism industry and to a certain extent to make up for the lack of land input elements [32]. The main sports industry unit is a vital carrier for the development of sports industry and a key indicator to reflect the development scale of the industry.…”
Section: • Input Indexmentioning
confidence: 99%
“…Previous studies on urban tourism efficiency have mostly used data envelopment models (DEA). However, the traditional DEA model can only measure efficiency values up to 1, making it difficult to effectively rank urban points and neglecting the impact of slack variables on efficiency measures [40]. In contrast, the Super-SBM model considers slack variables and fully measures the previously unmeasurable efficiency value of spillover effects of urban points.…”
Section: Super-sbm Modelmentioning
confidence: 99%
“…Following the studies of existing scholars [40][41][42], this research considers the cross-attributes of the tourism industry and data availability, and selects the number of A-class scenic spots, the number of employees in accommodation and catering above the quota, and the number of travel agencies in each city as resource input factors (i.e., tourism resource endowment), labor input factors (i.e., tourism labor advantage), and capital input factors (i.e., tourism capital advantage), respectively. The total tourism revenue (i.e., tourism revenue capacity) and the total number of tourist arrivals (i.e., tourism market scale) of each city are chosen as output evaluation indicators.…”
Section: Super-sbm Modelmentioning
confidence: 99%
“…Using a spatial economic regression, Yang et al (2022) set out to identify the elements that are likely to influence tourism efficiency using the panel data of 30 provinces in China. The results suggested that different parts of the selected provinces offer a varying degree of efficiency based on a number of factors such as patents held, traffic congestion levels, financial structures, and governmental issues.…”
Section: Literature Reviewmentioning
confidence: 99%